Spatial Unit Roots in Regressions: A Practitioner's Guide and a Stata Package - Sascha O. Becker; P. David Boll; Hans-Joachim Voth (Institute of Labor Economics (IZA), 2025)
Spatial unit roots can lead to spurious regression results. We present a brief overview of the methods developed in Müller and Watson (2024) to test for and correct for spatial unit roots. We also introduce a suite of Stata commands (-spur-) implementing these techniques. Our commands exactly replicate results in Müller and Watson (2024) using the same Chetty et al. (2014) data. We present a brief practitioner's guide for applied researchers.
Keywords: C21; C22; C52; C87; N0; P0; R12; R15; 330; spurtest; spurious spatial regression; spatial unit roots; spurtransform